Ammonia Dynamics in the Human Body: Insights in Biomedical Sensing Technologies (Adv. Sensor Res. 7/2025) - Nijkoops, Annelot; Ciocca, Manuela; Costa Angeli, Martina Aurora; Pogliaghi, Silvia; Krik, Soufiane; Avancini, Enrico; Münzenrieder, Niko; Lugli, Paolo; Petti, Luisa (Advanced Sensor Research, 2025)
Biomedical Sensing Technologies Ammonia (NH3) is a key biomarker in diagnostics, and sensors play a crucial role in its detection to improve medical diagnosis. In article 2400179, Annelot Nijkoops, Luisa Petti, and co‐workers highlight recent advances in NH3 sensing technologies and explores future research directions, including advancements in breath sensing, as well as in vitro and in vivo sensing.